Pesantren and the Freedom of Thinking: Study of Maâhad Aly Pesantren Sukorejo Situbondo, East Java, Indonesia - Gazali, Hatim; Malik, Abd. (Al-Jamiah: Journal of Islamic Studies, 2009)
Various studies on Pesantren have been conducted through various lenses and perspectives; however, its attractiveness is still there. In some points, the pesantren is well known as a conservative institution in which freedom of thinking is limited. This article is willing to show that not all pesantrens limit their students freedom of thinking. One of them is Mahad Aly (higher education), one of the education institution in Pesantren Salafiyah Syafiiyah Sukorejo Situbondo which focuses its teaching on fiqh. Fiqh, or Islamic jurisprudence, is one of the branches of Islamic science. In some pesantrens, the teaching of fiqh is limited to one school or madhhab, particularly school of Shafii. However, in Mahad Aly, not only one school of thought is taught, but fiqh of four schools of thought. It shows a high tolerance and respect for differences. In order to seek a new ingredient in formulating Islamic law, the teaching of fiqh is combined with other sciences such as philosophy, sociology, and anthropology. This new ingredient produces a rich discourse of fiqh and widens its scope of discussion to include to religious relationships, gender, human rights, ecology, and other contemporary issues such as interfaith marriage, the possibility of a non-Muslim being president, and the role of women in the public sphere. Looking from the curriculum, the method of teaching, and the publication of bulletin of Tanwirul Afkar, this article proves that freedom of thinking is well-maintained at Mahad Aly.